ЭЛЕКТРОПРИВОДЫ МАЛОЙ МОЩНОСТИ НА ОСНОВЕ БЕСКОНТАКТНЫХ ДВИГАТЕЛЕЙ С ПОСТОЯННЫМИ МАГНИТАМИ - Акинин, К.П. (Інститут електродинаміки НАН України, Київ, 2011)
The paper is concerned with the developments of low power electric drives on the basis of permanent magnet brushless motors. Parameters of brushless motors are given. Functional schemes of the electric drives on the basis of permanent magnet brushless motors are described. References 6, table 1, figures 2.